The Influence of Catalyst Loading on Electrocatalytic Activity and Hydrogen Production in PEM Water Electrolysis - Rohendi, Dedi; Amelia, Icha; Sya'baniah, Nyimas Febrika; Yulianti, Dwi Hawa; Syarif, Nirwan; Rachmat, Addy; Fatmawati; Majlan, Edy Herianto (Science and Technology Indonesia, 2024)
The climate change caused by the widespread and continuous use of fossil fuels is a problem that needs to be addressed urgently. One of the solutions offered is through an energy transition towards the use of new or renewable and low-carbon fuels. Hydrogen gas as a carrier of energy is an alternative solution that has attracted the attention of researchers, due to its high combustion energy and environmental friendliness. The production of hydrogen gas using the Proton Exchange Membrane Water Electrolysis (PEMWE) method is considered effective for large-scale production. This study investigates the impact of catalyst loading and various current densities on hydrogen production in the PEM water electrolysis process, utilizing the Cu2O/C catalyst. This study investigates the impact of catalyst loading and different current densities on hydrogen production in the PEM water electrolysis process, utilizing the Cu2O/C catalyst. The electrode catalytic properties were evaluated using the Cyclic Voltammetry (CV) method to determine the Electrochemical Surface Area (ECSA) and the Electrochemical Impedance Spectroscopy (EIS) method to determine the electrical conductivity. The ECSA and EIS measurements demonstrated that the best results were obtained at a higher catalyst loading of 2 mg/cm2 with an ECSA value of 0.21 m2/g and electrical conductivity of 3.04 × 10−6 S/cm. The production of hydrogen results showed that the highest hydrogen production rate was 3.75 mL/s with a catalyst loading of 2.5 mg/cm2, indicating that increasing the load could lead to a higher rate of hydrogen gas production, but this is highly dependent on the surface area utilized. Additionally, at higher current densities, the cell resistance in the electrolysis process may decrease, leading to reduced electrode efficiency for hydrogen production. Thus, the use of high currents may not always be advantageous in hydrogen production using the PEM water electrolysis method.